An investigation into how participation in science expo projects influences grade 9 learners' dispositions towards science learning: a case study - Musekiwa, Beatrice K (Rhodes University, Faculty of Education, Department of Education, 2016)
There has been increasing participation of learners from disadvantaged backgrounds in competitive events like the Eskom Science Expo over the past few years. It is against this backdrop that this study sought to find out how some grade 9 learners' participation in science expo projects influences their disposition towards science. In the context of this study, disposition refers to how learners view themselves in relation to science learning as a result of participating in science expos. The study is underpinned by an interpretative paradigm and I made use of a qualitative case study. My research participants were five grade 9 learners from two secondary schools in Grahamstown in the Eastern Cape Province of South Africa. I used observations, semistructured interviews and learners' journals for my data collection. To analyse the data I used the inductive approach where I made use of themes emerging from the data. The social learning theory described by Vygotsky (1978) is the guiding theory in the research with a focus on mediation of learning and the zone of proximal development (ZPD). The main findings from my study were that indeed participation in science expos does influence the disposition of learners towards science among the grade 9 learners. I also found an improved understanding of scientific concepts as the learners interacted with science in everyday and familiar contexts. Lastly, doing projects that are close to learners' interests resulted in them enjoying doing science more. The learners' science expo projects contribution to the Grahamstown community is of no small value, as has already been seen by the achievement of previous participants. The current group is already showing their impact and influence of the science"“expo project involvement in terms of their performance in their classrooms and in their awareness of their role as young 'scientists'. I therefore recommend that more learners be encouraged to take part in such projects as the science-expo projects not only improve learners' understanding of the subject matter but also encourages a positive shift in their attitude towards science learning. It also enhances their understanding by allowing the young learners to interact with their environment to find solutions to problems that the community might be faced with, for example, water shortages and sustainable development initiations like gardening and the proper use of naturally acquired water resources.
Keywords: Uncatalogued